Impact study of composite scarf joints with interspersed particles - Tan, Adrian Tze En (2013)
In this Final Year Project (FYP), the impact properties of scarf repair were enhanced with the application of Core Shell Polymer (CSP) particles at a density of 30g/m2 to the interply interfaces of the central repair patch. The application of CSP particles is expected to improve impact properties through 2 mechanisms; 1) improving elastic energy absorption which has the greatest potential of reducing extent of damage in a laminate and 2) reduction or elimination of stiffness mismatch faced in a typical scarf repair. In the first phase of the project, the ability of CSP particles to enhance elastic energy absorption was looked at. Glass Fiber Reinforced Polymer (GFRP) samples, both reference and CSP-modified, were impact tested with energy of 17J and 12.5J. A reduction in elastic energy absorption in the modified samples at 17J coupled with an increase in elastic energy absorption at a lower energy of 12.5J, served to suggest that the CSP particles have an elastic limit beyond which the effectiveness of the particles to improve elastic energy absorption is reduced.